Draft Annual Plan 1990-91 Volume VII Government of Assam - Planning Commission (Planning Commission, 1990)
The total area of Karbi Anglong Hill District and N .C. Hills District is 15,222 Sq. Km which constitutes 19.4% of the state area. The gross cultivable and net cropped area of the hill districts are 237.83 thousand hect. and 197.53 thousand hect respectively as indicated in Annexure-I.
Government of Assam
Government of Assam